(untitled) (ЕтноАнтропоЗум, 2015)
Throughout different examples regarding the effects of several practices or techniques for documenting the research problem (field notes and recording) certain positivistic assumptions are being reexamined about what can be referred as evidence in Macedonian qualitative research. Actually, the text confronts the feather-bedding of one kind of evidence over against other, respectively it stresses the importance of the researcher’s experience as evidence of validity in whatever practice of documenting.